Blood pressure trajectory of inpatient stroke rehabilitation patients from the Determining Optimal Post-Stroke Exercise (DOSE) trial over the first 12 months post-stroke - Hung, Stanley H.; Tierney, Christopher; Klassen, Tara D.; Schneeberg, Amy; Bayley, Mark T.; Dukelow, Sean P.; Hill, Michael D.; Krassioukov, Andrei; Pooyania, Sepideh; Poulin, Marc J.; Yao, Jennifer; Eng, Janice J. (Frontiers in Neurology, 2023)
Background High blood pressure (BP) is the primary risk factor for recurrent strokes. Despite established clinical guidelines, some stroke survivors exhibit uncontrolled BP over the first 12 months post-stroke. Furthermore, research on BP trajectories in stroke survivors admitted to inpatient rehabilitation hospitals is limited. Exercise is recommended to reduce BP after stroke. However, the effect of high repetition gait training at aerobic intensities (>40% heart rate reserve; HRR) during inpatient rehabilitation on BP is unclear. We aimed to determine the effect of an aerobic gait training intervention on BP trajectory over the first 12 months post-stroke. Methods This is a secondary analysis of the Determining Optimal Post-Stroke Exercise (DOSE) trial. Participants with stroke admitted to inpatient rehabilitation hospitals were recruited and randomized to usual care (n = 24), DOSE1 (n = 25; >2,000 steps, 40–60% HRR for >30 min/session, 20 sessions over 4 weeks), or DOSE2 (n = 25; additional DOSE1 session/day) groups. Resting BP [systolic (SBP) and diastolic (DBP)] was measured at baseline (inpatient rehabilitation admission), post-intervention (near inpatient discharge), 6- and 12-month post-stroke. Linear mixed-effects models were used to examine the effects of group and time (weeks post-stroke) on SBP, DBP and hypertension (≥140/90 mmHg; ≥130/80 mmHg, if diabetic), controlling for age, stroke type, and baseline history of hypertension. Results No effect of intervention group on SBP, DBP, or hypertension was observed. BP increased from baseline to 12-month post-stroke for SBP (from [mean ± standard deviation] 121.8 ± 15.0 to 131.8 ± 17.8 mmHg) and for DBP (74.4 ± 9.8 to 78.5 ± 10.1 mmHg). The proportion of hypertensive participants increased from 20.8% (n = 15/72) to 32.8% (n = 19/58). These increases in BP were statistically significant: an effect [estimation (95%CI), value of p] of time was observed on SBP [0.19 (0.12–0.26) mmHg/week, p < 0.001], DBP [0.09 (0.05–0.14) mmHg/week, p < 0.001], and hypertension [OR (95%CI): 1.03 (1.01–1.05), p = 0.010]. A baseline history of hypertension was associated with higher SBP by 13.45 (8.73–18.17) mmHg, higher DBP by 5.57 (2.02–9.12) mmHg, and 42.22 (6.60–270.08) times the odds of being hypertensive at each timepoint, compared to those without. Conclusion Blood pressure increased after inpatient rehabilitation over the first 12 months post-stroke, especially among those with a history of hypertension. The 4-week aerobic gait training intervention did not influence this trajectory.